INVENTARISASI KUPU-KUPU DI UNIVERSITAS NEGERI MEDAN - Elida Hafni Siregar; Halim Simatupang (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2017)
This reseach aims to known the butterflies species at State University of Medan. Observation and collection of  butterflies  were conducted from March – April 2016 at State University of Medan. Butterflies observation  conducted with scan sampling method at 09:00 to 17:00 in sunny days. This study consist of  found 43 species of butterflies, belonging to 5 families, i.e. Pieridae, Papilionidae, Nymphalidae, Lycaenidae, and Hesperiidae. 15 species of butterflies are found in only one site but 2 species are found in all sites, i.e. Appias olferna and Papilio polytes.